Comparison of Modes of Survey Administration in Assessing Hepatitis B Knowledge, Attitudes and Practices Among the Myanmar Community in Perth, Western Australia - Phoo, Nang Nge Nge (Curtin University, 2023)
This thesis presents the development of a web-based survey application, i.e., an audio computer-assisted self-interview with illustrated pictures. The application was tested against traditional survey modes in collecting hepatitis B knowledge, attitudes and practices among the Myanmar community in Perth. The thesis adds to the literature knowledge of developing a survey application and the survey mode comparison results in a survey of sensitive topics among a migrant community with highly diverse cultural and linguistic backgrounds.